Effectiveness Purple Sweet Potato Capsules on the HDL of the ASN in Sorong City Government with Central Obesity - Mustamir Kamaruddin; Wilma Florensia; Muhammad Reza Januar; Louse Lusiana Lapon; Tertiana Angelina Hutauruk (Institute of Computer Science (IOCS), 2022)
Central obesity fat distribution is influenced by sex hormones and occurs mostly in men and has a strong relationship and is a better indicator of changes in HDL. This study aims to assess the effect of giving purple sweet potato capsules to HDL levels in central obesity of ASN in Sorong City Government. This type of research is a quasi-experimental design with a pre-post control group design. The research sample was male civil servants at the Sorong City Government, taken by purposive sampling method with a sample size of 34 people who were divided into 2 groups. The treatment group was given purple sweet potato capsules with a capsule weight of 250 mg/capsule which was consumed 4 capsules/day for 45 days (6 weeks), while the control group was given capsules containing roasted wheat flour. HDL levels were measured before and after the intervention. Food intake of both groups was obtained by semi-quantitative food frequency and food recall methods. Statistical analysis used was paired t test, independent t test, and ANOVA test. In the treatment group there was an increase in HDL levels of 4.12 mg/dl (10.9%) and statistically showed there was a difference before and after the intervention p = 0.00. To the government to encourage people to pay more attention to their health status and pay more attention to the availability of local food that is beneficial to the health status of the community.